Relationship between coping behavior and students’ perceptions of the passage of time - Viktor Volodymyrovych Plokhikh (Insight: the psychological dimensions of society, 2023)
Despite the significant increase in academic load and the general complication of daily life, a modern student should be able to overcome stressful situations and complete tasks on time. The study’s purpose was to empirically determine the basis and features for the distinctive correlations between the students’perceptions of time passing and the selection of coping behavior options. Methods. The study included 139 university students as participants. The empirical study applied the following standardized test methods: “Coping behavior in stressful situations”, the scale “Competence in time” from the Personality Self-Actualization Test, the “Scale of experiencing time”, and the Freiburg Personality Inventory (form B). For statistical data processing, cluster analysis, Spearman’s correlation analysis, and the Mann-Whitney U-test were used. Results. Competence in time in the group was related to group perceptions of time flow as quick (rs=-.188; p=.027), limited (rs=-.265; p=.002), and – at the trend level – as filled (rs=.143; p=.093)and diverse (rs=.157; p=.064). Using cluster analysis, subgroups 1 (n=64) and 2 (n=75) in the group were distinguished. The advantages of Subgroup 1 over Subgroup 2 in terms of time competence (U=172.00;p<.001) and balance (U=708.00; p<.001) were established. Subgroup 1 subjects were more focused on avoidance (U=1811.00; p=.013) and distraction(U=1861.00; p=.022) coping, while Subgroup 2 subjects were more focused on the emotional response to stress(U=1120.00; p<.001). It was discovered that subjects in Subgroup 2 had relatively stronger perceptions of time limited (U=1762.00; p=.006) and fragmented(U=1983.50; p=.073). In a group, task-oriented coping was associated with perceptions of time passing as quick (rs=.183; p=.031), filled (rs=.361; p<.001), pleasant (rs=.182; p=.032), diverse (rs=.175; p=.040), and organized (rs=.296; p<.001); emotion-oriented coping was associated with perceptions of time passing as quick (rs=.208; p=.014), jumpy (rs=.256; p=.002), fragmented (rs=.222; p=.009), and limited (rs=.182;p=.032). Conclusions. The subjects’ comprehensive positive perception of the present moment (as filled, limitless, and slow-flowing) was associated with preferring consciously managed, acceptable in a stressful situation coping behavior options. Students’ emotionally oriented coping behavior was directly related to problematic personality traits and perceptions of fragmentation and disintegration of the passage of time. The insufficient integrity of the personal experience that was being formed, related to the perceptions of the passage of time as filled, pleasant, diverse, organized, but also fleeting, limited students’ use of coping focused on solving tasks in stressful situations.